Multiple palmar epidermoid cysts: fourth reported case - Gautam, Raj; Shaikh, Tanveer Parvez; Gupta, Shitiz; Wani, Jatin; Murali, Sridevi; Bhupatkar, Ankit; Deolekar, Sandesh (International Journal of Research in Medical Sciences, 2017)
Implantation of epidermal fragments into the dermis has been pointed out as the cause of common epidermal cysts. However, some palmoplantar epidermoid cysts have been reported to be caused by human papillomavirus (HPV) infection or to be derived from eccrine ducts. A 55 year old woman presented with multiple epidermoid cysts on the palm and volar aspect of her left hand. HPV infection CEA was not detected in situ hybridization and polymerase chain reaction.